CARA MUDAH MENGUKUR ARAH KIBLAT - Arianti, Farida (JURIS (Jurnal Ilmiah Syariah), 2010)
To measure the accurate direction for prayer (kiblat) is not a simple matter for every Moslem, especially for the ordinary ones. Therefore, this article is intended to explain and give simple understanding  on how to use and practice as well  the nature of Qiblat measurement wherever the moslems are. Actually, there are some ways to measure the accurate direction of qiblat. However, many of them are quite complicated to practice. Finally, using compass is believed to be easier and others seem to be forgotten.